Risk Factors for Acute Kidney Injury in Critically Ill Neonates: A Systematic Review and Meta-Analysis - Hu, Qian; Li, Shao-Jun; Chen, Qian-Ling; Chen, Han; Li, Qiu; Wang, Mo (Frontiers in Pediatrics, 2021)
ABSTARCT Background and objective Acute kidney injury (AKI) is recognized as an independent risk factor for mortality and long-term poor prognosis in neonates. The objective of the study is to identify the risk factors for AKI in critically ill neonates to provide an important basis for follow-up research and early prevention. Methods The PubMed, Embase, Web of Science, Cochrane Library, China National Knowledge Infrastructure, WanFang Med, SinoMed, and VIP Data were searched for studies of risk factors in critically ill neonates. Studies published from the initiation of the database to November 19th, 2020 were included. The quality of studies was assessed by the Newcastle-Ottawa Scale and Agency for Healthcare Research and Quality checklist. The meta-analysis was conducted with STATA 15 and drafted according to the PRISMA guidelines. Results Seventeen studies (five cohort studies, ten case-control studies and two cross-sectional studies) were included in meta-analysis, with 1627 cases in the case group and 5220 cases in the control group. The incidence of AKI fluctuated from 8.4% to 63.3%. Fifteen risk factors were included, nine of which were significantly associated with an increased risk of AKI in critically ill neonates: gestational age (SMD=-0.31, 95%CI=(-0.51, -0.12), P=0.002), birthweight (SMD=-0.37, 95%CI=(-0.67, -0.07), P=0.015), 1-minute Apgar score (SMD=-0.61, 95%CI=(-0.78, -0.43), P=0.000 ), 5-minute Apgar score (SMD=-0.71, 95%CI=(-1.00, -0.41), P=0.000), congenital heart disease (OR=2.94, 95%CI=(2.08, 4.15), P=0.000), hyperbilirubinemia (OR=2.26, 95%CI=(1.40, 3.65), P=0.001), necrotizing enterocolitis (OR=6.32, 95%CI=(2.98, 13.42), P=0.000), sepsis (OR=2.21, 95%CI=(1.25, 3.89), P=0.006), mechanical ventilation (OR=2.37, 95%CI=(1.50, 3.75), P=0.000). Six of them were not significantly associated with AKI in critically ill neonates: age (SMD=-0.25, 95%CI=(-0.54, 0.04), P=0.095), male sex (OR=1.10, 95%CI=(0.97, 1.24), P=0.147), prematurity (OR=0.90, 95%CI(0.52, 1.56), P=0.716), cesarean section (OR=1.52, 95%CI(0.77, 3.01), P=0.234), prenatal hemorrhage (OR=1.41, 95%CI=(0.86, 2.33), P=0.171), vancomycin (OR=1.16, 95%CI=(0.71, 1.89), P=0.555). Conclusions This meta-analysis provides a preliminary exploration of risk factors in critically ill neonatal AKI, which may be useful for the prediction of AKI.